The Impact of Bacterial Leaf Blight Disease (Pantoea agglomerans) on Grain Yield and Nutritional Quality of Oat - Ruochen Zhang; Jianjun Wang; Longhai Xue; Malik Kamran; Yue Wang; Xuekai Wei; Guiqin Zhao; Chunjie Li (Microorganisms)
As an important cereal and feed crop, oat has significant economic value and is widely cultivated throughout the world. However, leaf diseases have become a crucial factor limiting the increase in oat grain yield and the optimization of its nutritional quality. Among these, the bacterial leaf blight disease (LBD) caused by Pantoea agglomerans has been an emerging and prevalent oat disease in Northwest China in recent years and has become a major challenge for oat cultivation in this region. This study was designed to investigate the effects of LBD on grain yield and nutritional quality of two common oat varieties, i.e., Avena nuda “Baiyan 2” (B2) and A. sativa “Baiyan 7” (B7), in greenhouses. The results showed that after infection causing LBD, the growth, grain yield and nutritional indexes (except the fiber content) of B2 and B7 were significantly reduced (p < 0.05), with grains per spike, thousand grain weight, protein, and β-glucan reduced by 14.2%, 5.5%, 12.9% and 21.5%, respectively. In contrast, the average fiber content of the infected oats increased by 8.4%. In addition, both with and without infection, the grain yield of B7 was higher than that of B2, while the nutritional quality of B2 seeds was superior to that of B7 seeds. This study provides a scientific basis for LBD control and the variety selection of oat, promoting the sustainable development of the oat industry.